TAʾṮĪR QIRĀʾAH AL-MURABBAʿI FĪ TAʿLĪM AL-QIRĀʾAH - Rusmilawati Ahmad (Jurnal Al-Maqoyis, 2020)
Abstract:The aims of this research are: To study how to apply and influence the strategy of square or text cut and Broken Square / Text & Index Card Match for Islamic high school students in Balangan.The research design used in this study was an experimental research design.The results of this study are 1) during the implementation of the Broken Square / Text & Index Card Match strategy, it can be seen that there is a change in the learning patterns of students who answer the questions asked by the researcher, in addition, they are also more enthusiastic and active in working on the assigned task. Poor activity also tends to decrease and 2) the effect on learning outcomes is found by students about Broken Square / Text & Index Card Match at  Madrasah Tsanawiyah Negeri 3 Balangan and Madrasah Tsanawiyah Al Hidayah Inan Paringin Selatan according to the test results was 0.00 is smaller than the significance score α = 0.05, this indicates that Ha is accepted and H0 is rejected.